From Aggregation to Transformation: Plato's Critique of Preference-Based Politics - Ogelenya,, Grace (dialektika kontemporer, 2025)
This paper provides a critical examination of how Plato's concept of the enlightened self offers a profound and transformative alternative to the foundational premises of modern social contract theories. Through a rigorous textual analysis of The Republic and other relevant dialogues, combined with a critical engagement with contemporary scholarship, this research identifies and elaborates upon four key dimensions of this Platonic framework: the role of philosophical education in transcending narrow self-interest, the intrinsic connection between individual enlightenment and the realization of political justice, the knowledge-based (epistemic) foundations of legitimate social structures, and the goal-oriented (teleological) nature of Plato's political vision. The findings demonstrate that Plato's approach constitutes a fundamental departure from modern contractarian theories by focusing on philosophical transformation rather than on the aggregation of pre-existing, stable preferences. For Plato, political legitimacy originates not from a calculated agreement among self-interested individuals but from a shared recognition of objective goods that are achievable only within a properly ordered political community. This research concludes that Plato’s political philosophy offers not a simple rejection of contractarian thinking but provides an alternative foundation for political legitimacy based on a transformed self-understanding. This perspective addresses significant limitations in conventional contractarian approaches while robustly supporting the conditions for genuine individual flourishing within the political community.